MANAGEMENT ACCOUNTING SYSTEMS, INTELLECTUAL CAPITAL AND PERFORMANCE: AN INTEGRATED APPROACH - Novas, Jorge (2015)
The purpose of this study is to empirically test the relationship between management accounting systems (MAS), intellectual capital (IC) and organizational performance. It is highlighted the role of MAS as information networks that collect, process and communicate information that influence the development of IC, as well as networks of relationships that support the establishment of conditions for the creation and integration of organizational knowledge. An arguably complete framework of the relations between MAS, IC and performance is developed and empirically tested using structural equation modelling. A questionnaire was developed to conduct a survey of senior managers of Portuguese companies. The study provides an integrated view of the relations between MAS, IC and performance, from which are deduced strong interdependencies between variables. Statistical support was found for six out of nine hypothesized relationships, allowing at a clear evidence of the ability of MAS to assist the development of the different dimensions of IC and therefore IC as a whole.